Sag Harbor Home - George Santulli (US Department of State):::Creator::::::::::::
Bell & chime hanging from tree near Steinbeck's cottage, in Sag Harbor, New York. This was taken during a tour with Georgian documentarians. Digital copy only. No hard copy.